(3CShGb GdCThGb ef eUGQY GdYTGbs - (3EHQGgje Hf YeQ Hf MSf GdoQnHGW Hf Ydj Hf CHj HcQ GdHbGYj, CHh GdMSf HQgGf GdOjf , (B885 (3g` s; (3bQg SfGf , jhSa Hf YHO Gdedc Hf YHO GdZahQ, SfGf GdOjf,J (B852 (3g` s ((3SGde GdSfghQj GdeGdcj s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hgh MSHj hfYe Gdhcjd gPG ajef CSJOQLg Gdghi Gdecfhf, hJhGdJ Ydjg CdhGfg hGdafhf MJi hUd Edi MjR GdLfhf s
(3BNQgG (B:s
(3HKeOjf dGMJ fGQ djdi hUMHJj HaQY GdZVG JRLj GdbdGU GdMhGejG gPG eG CQOJ EKHGJg bO jSQg Gddg hdg GdMeO MSHfG Gddg hfYe Gdhcjd s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B241 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B316s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B28 s
Keywords: (3GdCOHs